2016
DOI: 10.1002/eqe.2733
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic collapse resistance and residual drift assessment of buildings with fluidic self‐centering systems

Abstract: SUMMARYThe seismic performance of three-and six-story buildings with fluidic self-centering system is probabilistically assessed. The fluidic self-centering systems consist of devices that are based on the technology of fluid viscous dampers but built in a way that pressurization of the devices results in preload that is explored to reduce or eliminate residual drift. The design of these buildings followed a procedure that parallels the design for structures with damping systems in ASCE 7 but modified to inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 37 publications
2
30
0
Order By: Relevance
“…2,[5][6][7] Using realistic models of entire structures captures the residual drift trends for different structural systems, including the influence of MDOF effects. The first approach relies on numerical analysis of representative multi-story buildings to draw statistical inferences on the residual drift.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,[5][6][7] Using realistic models of entire structures captures the residual drift trends for different structural systems, including the influence of MDOF effects. The first approach relies on numerical analysis of representative multi-story buildings to draw statistical inferences on the residual drift.…”
Section: Introductionmentioning
confidence: 99%
“…This approach has been used to examine the residual drift performance of specific, conventional, or high-performance structures. 2,[5][6][7] Using realistic models of entire structures captures the residual drift trends for different structural systems, including the influence of MDOF effects. However, the statistical models developed in these studies are usually very case specific and/or require an independent calibration when applied to a system that differs even slightly from the one used in the study.…”
mentioning
confidence: 99%
“…It was concluded that greater magnification factors increased failure probability of the dampers as well as collapse probability of the structure. Likewise, the collapse performance of the fluidic self‐centering system was also studied by Kitayama et al incorporating the ultimate behavior of this device …”
Section: Introductionmentioning
confidence: 99%
“…Due to the excellent characteristics of self-centering structures, they are widely applied in engineering practices. Therefore, the seismic design method of such structures has attracted more and more attentions of the structural earthquake engineering community as well (Eatherton et al, 2014; Kitayama and Constantinou, 2016b; Liu et al, 2018; Qiu and Zhu, 2017a).…”
Section: Introductionmentioning
confidence: 99%